2021
DOI: 10.1007/s11357-021-00396-0
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and tendon adaptations to moderate load eccentric vs. concentric resistance exercise in young and older males

Abstract: Resistance exercise training (RET) is well-known to counteract negative age-related changes in both muscle and tendon tissue. Traditional RET consists of both concentric (CON) and eccentric (ECC) contractions; nevertheless, isolated ECC contractions are metabolically less demanding and, thus, may be more suitable for older populations. However, whether submaximal (60% 1RM) CON or ECC contractions differ in their effectiveness is relatively unknown. Further, whether the time course of muscle and tendon adaptati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 77 publications
3
49
0
2
Order By: Relevance
“…Interestingly, both Franchi et al (2014) and Seger et al (1998) found regional hypertrophy in the central region of the VL ACSA (11%) and total quadriceps ACSA (3.4%) after CT, respectively. Increases in quadriceps muscle volume were also observed by Quinlan et al (2021) after only 4 weeks of submaximal CT performed for 8 weeks with a leg press in young (mean age: 23.3 years) and older males (mean age: 69.1 years).…”
Section: Concentric-only Strength Trainingmentioning
confidence: 82%
See 4 more Smart Citations
“…Interestingly, both Franchi et al (2014) and Seger et al (1998) found regional hypertrophy in the central region of the VL ACSA (11%) and total quadriceps ACSA (3.4%) after CT, respectively. Increases in quadriceps muscle volume were also observed by Quinlan et al (2021) after only 4 weeks of submaximal CT performed for 8 weeks with a leg press in young (mean age: 23.3 years) and older males (mean age: 69.1 years).…”
Section: Concentric-only Strength Trainingmentioning
confidence: 82%
“…In contrast, no change in Achilles tendon stiffness was reported after 6 weeks of a heel-drop regimen (Morrissey et al, 2011). In the previous studies, the Patella tendon CSA and length remained unchanged (Malliaras et al, 2013;Quinlan et al, 2021), while increases in Patella tendon CSA (+14.9%) were found after a 12-week CT performed with whey protein supplementation (Farup et al, 2014b).…”
Section: Concentric-only Strength Trainingmentioning
confidence: 83%
See 3 more Smart Citations